Peran Penting Posisi Matahari Dalam Penentuan Rashdul Qiblat Lokal dan Global - lestari, tina; Ramadhan, Rizal (UIN ALAUDDIN MAKASSAR, 2024)
The determination of the direction of Qibla in Islam plays an important role in determining the direction of the Kaaba in Makkah, Saudi Arabia, which is a reference for Muslims in carrying out prayers. The position of the Sun plays an important role in determining the direction of Qibla, especially in the local and global Qibla Rashdul method. The local Qibla Rashdul uses the daily position of the Sun when crossing or passing through the city of Mecca, while the global Qibla Rashdul utilizes the position of the Sun globally to determine the direction of the Qibla. In determining the direction of Qibla, the position of the Sun is used as a reference to determine the direction of the Kaaba, which is then used as a reference in performing prayers. Developments in the direction of Qibla that continue to take place along with the development of technology and knowledge, allow Muslims to determine the direction of Qibla more accurately and easily.